Early Alpha-Fetoprotein Response Is Associated With Survival in Patients With HBV-Related Hepatocellular Carcinoma Receiving Lenvatinib - Liu, Bo; Shang, Xiao; Shi, Jin-Yu; Cui, Guo-Zhen; Li, Xi; Wang, Nan-Ya (Frontiers in Oncology, 2022)
Background/purpose: Lenvatinib is a first-line treatment for unresectable hepatocellular carcinoma (uHCC). We assessed the value of early alpha-fetoprotein (AFP) response for predicting clinical outcomes with lenvatinib treatment in patients with HBV-related uHCC and elevated AFP levels. Methods: This retrospective analysis included patients with HBV-related uHCC and baseline AFP levels ≥20 ng/ml who received lenvatinib for >1 month between November 2018 and May 2021. Early AFP response was defined as a >20% decrease in AFP serum level from baseline after 4 weeks of lenvatinib treatment. Radiological response (Response Evaluation Criteria in Solid Tumors v1.1), progression-free survival, and overall survival were assessed in AFP responders and non-responders. Results: Of the 46 patients analyzed, 30 (65.2%) were early AFP responders and 16 (34.8%) were non-responders. Compared to the non-responders, early AFP responders had a significantly higher objective response rate (34.5% vs 6.3%, p=0.0349), disease control rate (82.8% vs 50.0%; p=0.0203) and longer median progression-free survival (13.0 vs 7.0 months; HR, 0.464; 95% CI, 0.222-0.967; p=0.028). A subsequent multivariate analysis confirmed that early AFP response (HR, 0.387; 95% CI, 0.183-0.992; p=0.0154), Eastern Cooperative Oncology Group Performance Status of 0 (HR, 0.890; 95% CI, 0.811-0.976; p=0.0132) and Albumin-Bilirubin grade 1 (HR, 0.457; 95% CI, 0.269-0.963; p=0.0327) were independent prognostic factors for longer progression-free survival. Conclusion: AFP is an important prognostic factor and a predictive biomarker for survival benefit with lenvatinib treatment in patients with HBV-related uHCC.